Leasing a efektywność substytucji pracy przez kapitał w przedsiębiorstwie produkcyjnym - Przepióra, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The phenomenon of the scarcity of resources is common. This issue involves the problem of substitution of capital for labour. The thesis made in the first part of the publication states that the comparison of saved labour cost to lease payment can be the criterion of the profitability of substitution. Admittedly the cost of leasing and the cost of employment could be a key factor in the evaluation of the efficiency of substitution. But there is no doubt that the problem should be seen wider. Examining all elements of work system (as designed by G. Nadler) is a correct approach. The measure of examined effectiveness should be efficacy (defined as how close we get to achieving partial objectives), profitability (defined as the difference between the result and the costs) and economicness (the ratio of the result to the costs). (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 408-417